Non-invasive blood oxygenation monitoring from different sites of human body using diffuse reflectance spectroscopy: a feasibility study of diabetic foot monitoring - Kumar, Ajay; Chellappan, Kallaivani; Nasution, Aulia; Kanawade, Rajesh (SPIE, 2021)
Diabetic foot ulcer is one of the most common causes of lower-extremity amputation of diabetic patients worldwide. Researchers have identified several optical diagnostic techniques to diagnose diabetic foot ulcer by monitoring average blood oxygenation state in the foot tissue. However, they need sophisticated equipment and specialized expertise. In addition, they may not be able to resolve the relative local blood volume fraction of reduced/- oxyhemoglobin within the bulk of highly scattering tissue media. Therefore, aim of the study is to extract localized blood volume fraction of reduced/-oxyhemoglobin by using diffuse reflectance spectroscopy (DRS). To prove the feasibility of DRS for diabetic foot ulcer detection, we measured the localized blood volume concentrations of reduced hemoglobin (RHb), oxyhemoglobin (HbO2), and oxygen saturation (SO2) from different sites such as lips, earlobe, finger and foot of human subjects by using DRS. The measured average level of HbO2 and SO2 found highest in lips followed by a finger, earlobe, and foot, while the average level of RHb followed the reverse trend. Thus, the preliminary results suggest that the proposed approach could be used for real-time, accurate, and noninvasive monitoring of blood oxygenation parameters from the site of ulcerated foot that may help in early diagnosis, treatment planning, and monitoring of diabetic foot. This may reduce the health-care cost and improve the quality of life of diabetic foot patients.